Nature and nation forests and development in Peninsular Malaysia - Kathirithamby-Wells, Jeyamalar (University of Hawaiʻi Press, 2005)
Nature and Nation explores the relations between people and forests in Peninsular Malaysia where the planet's richest terrestrial eco-system met head-on with the fastest pace of economic transformation experienced in the tropical world. It engages the interplay of history, culture, science, economics and politics to provide a holistic interpretation of the continuing relevance of forests to state and society in the moist tropics. Malaysia has long been singled out for emulation by developing nations, an accolade contradicted in recent years by concerns over its capital-, rather than poverty-driven forest depletion. The Malaysian case supports the call for re-appraisal of entrenched prescriptions for development that go beyond material needs.